Whispers of a Secret: From Non-reception to New Life in Existential Media Studies – Speaking Into the Air in Sweden - Amanda Lagerkvist (Media Theory, 2022)
Upon arrival in Sweden, Speaking into the Air was not spoken about. Instead, it was whispered about—often with admiration, sometimes in perplexment. This article contextualizes the non-reception in light of three circumstances: the Swedish consensus culture in which dialogue is sacred, the role of media in the nation for disseminating the dialogical praxis and its results, and the Swedish model of media studies. The article shows how the book’s many open secrets (the stress on the simplicity of being there, human fragility, death and communication, embodiment and interruption) eventually provided the richest source of inspiration, as Speaking enjoyed new life in existential media studies.